Combined Experimental and CFD Investigation of the Parabolic Shaped Solar Collector Utilizing Nanofluid (CuO-H2O and SiO2-H2O) as a Working Fluid - Ketan Ajay; Lal Kundan (Journal of Engineering)
Nanoscience application plays a major role in heat transfer related problems. A nanofluid is basically a suspension of fine sized nanomaterials in base fluids like water, Therminol VP-1, ethylene glycol, and other heat transfer fluids. This paper evaluates the possible application of nanofluid in parabolic shaped concentrating solar collector using both experimental and CFD analysis. Different types of nanomaterials used are SiO2 and CuO of 20 nm average size. Nanofluids of SiO2-H2O (DI) and CuO-H2O (DI) of 0.01% volume concentration are used. Flow rates of 40 LPH and 80 LPH are used. ANSYS FLUENT 14.5 is used for carrying out CFD investigation. 3D temperature distribution of absorber tube is obtained using numerical investigation and the result is compared with the experimental one. Improvement in efficiency of collector of about 6.68% and 7.64% is obtained using 0.01% vol. conc. SiO2-H2O (DI) nanofluid and 0.01% vol. conc. CuO-H2O (DI) nanofluid, respectively, as compared to H2O (DI) at 40 LPH while at 80 LPH improvement in efficiency of collector of about 7.15% and 8.42% is obtained using 0.01% vol. conc. SiO2-H2O (DI) nanofluid and 0.01% vol. conc. CuO-H2O (DI) nanofluid, respectively, as compared to H2O (DI). Both experimental and CFD temperature results are in good agreement.